CHITOSAN BIOPOLYMER IN GLYPHOSATE ADSORPTION: USE IN ENVIRONMENTAL MONITORING OR REMEDIATION - Oliveira, G. R. [UNESP]; D'alevedo, L. B. [UNESP]; Lessa, S. S. [UNESP]; Caetano, M. M. M. [UNESP]; Goveia, D. [UNESP]; Tonello, P. S. [UNESP] (Centro Federal Educacao Tecnologica Rio Grande Norte, 2023)
In this work, low molecular weight chitosan was used to adsorb the herbicide glyphosate in aqueous solution. Considering the possibilities of remediation and monitoring in aquatic environments, chitosan was formatted into thin discs 0.8 mm thick and 2.5 cm in diameter. The films were characterized by SEM, EDS and FTIR. In the adsorption study, a chitosan disc was able to adsorb 100% of a 5 mgL(-1) glyphosate solution. Pseudo -first-order, pseudo-second-order and Elovich kinetic models were applied and it was found that chemisorption predominates in the adsorption process. Thus, chitosan films can act very well as a material for remediating water bodies contaminated by glyphosate. For monitoring studies, the possibility of using chitosan films in DGT (Diffusive Gradients in Thin Films) technique was verified and the diffusive material used was 1.5% agarose film (m/v). The diffusion coefficient of glyphosate in the agarose gel was determined 7.94 x 10(-10) m(2)s(-1).
Keywords: Adsorption; Chitosan; Environmental Monitoring; Glyphosate